Examining the mental health outcomes of school-based peer-led interventions on young people: A scoping review of range and a systematic review of effectiveness - King, Thomas (PLoS One, 2021)
Schools worldwide have implemented many different peer-led interventions with mixed results, but the evidence base on their effectiveness as mental health interventions remains limited. This study combines a scoping review and systematic review to map the variations of peer-led interventions in schools and to evaluate the quality of the existing evidence base. This scoping review and systematic review evaluated the existing literature across 11 academic databases. Studies were included if they reported a peer-led intervention that aimed to address a mental health or wellbeing issue using a peer from the same school setting. Data were extracted from published and unpublished reports and presented as a narrative synthesis. 54 studies met eligibility criteria for the scoping review, showing that peer-led interventions have been used to address a range of mental health and wellbeing issues globally. 11 studies met eligibility criteria for the systematic review with a total of 2,239 participants eligible for analysis (929 peer leaders; 1,310 peer recipients). Two studies out of seven that looked at peer leaders showed significant improvements in self-esteem and social stress, with one study showing an increase in guilt. Two studies out of five that looked at peer recipient outcomes showed significant improvements in self-confidence and in a quality of life measure, with one study showing an increase in learning stress and a decrease in overall mental health scores. The findings from these reviews show that despite widespread use of peer-led interventions, the evidence base for mental health outcomes is sparse. There appear to be better documented benefits of participation for those who are chosen and trained to be a peer leader, than for recipients. However, the small number of included studies means any conclusions about effectiveness are tentative.